Leading for public value in multi-agency collaboration. (January 2023) - Parker, Steven; Hartley, Jean; Beashel, Jim; Vo, Quoc
This paper examines the relationship between leadership and public value in a multi-agency service, requiring the delicate navigation of tensions when there are diverse and competing interests among public service collaborators. The paper adopts an actor-focused perspective arguing for the need to develop theory about leadership in collaborative settings which includes understanding political astuteness in leadership, as this can have an impact on whether or not public value is created. The setting is a multi-agency service hub and the empirical research is based on interviews and document analysis. The paper makes two contributions: first, it analyses the pluralistic leadership processes exercised in the pursuit of public value; secondly, it identifies how political astuteness is a key capability in leading diverse interest in cross-organisational collaborations.